Pikillacta, Huaro y la gran región del Cuzco: nuevas interpretaciones de la ocupación wari de la sierra sur - Glowacki, Mary; McEwan, Gordon (Pontificia Universidad Católica del Perú. Fondo Editorial, 2001)
Durante las últimas dos décadas han habido avances significativos en los estudios wari, como resultado de las investigaciones conducidas en las regiones provinciales. De esos estudios se han elucidado nuevas perspectivas sobre la expansión imperial de los wari, dándosele mayor énfasis a las investigaciones realizadas en los sitios monumentales de Pikillacta y Huaro. Basados en sus investigaciones, los autores han concluido que la ocupación wari fue más temprana, más intensa y de más larga duración que lo que previamente se impuso y plantean que su éxito se debió en gran parte al control directo del gobierno imperial de los wari.

Pikillacta, Huaro and the Greater Cuzco Region: New Interpretations of Wari Occupation in the Southern HighlandsOver the last two decades, significant advancements have been made in Wari studies, resulting primarily from investigations conducted in provincial regions that have elucidated new perspectives on Wari imperial expansion. This paper focuses on contributions made in the southern highlands Cuzco region, with particular emphasis on research carried out at the monumental sites of Pikillacta and Huaro. On the basis of their research, the authors offer a new interpretation of the Wari occupation of Cuzco, that it was earlier; more intense, and endured much longer than previously thought, and that the mechanism for its success was direct Wari imperial control.
Keywords: Arqueología; Pikillacta; Huaro; Cuzco; Imperio Wari; Sierra Sur; Archaeology; Pikillacta; Huaro; Cuzco; Wari Empire; Southern Highlands; https://purl.org/pe-repo/ocde/ford#6.01.02